Pembuatan Sediaan Tablet Mengapung Famotidin Menggunakan Kompleks Polielektrolit Kitosan-Pektin Sebagai Bahan Matriks - Sagita, Erny; Anwar, Effionora; Surini, Silvia (Majalah Ilmu Kefarmasian, 2011)
Floating tablet is one of the drug delivery system retained in the stomach which aims to prolong the lag time of the drug in the stomach. This principle can be used to improve the efficacy of famotidine in treating diseases in the stomach The purpose of this research is to develop dosage form afloat by using Chitosan Pectin Electrolytes (PEC) as matrix then used as the matrix in tablet dosage form with famotidine as a drug model. PEC also combined with hydroxypropylmethylcellulose (HPMC) with different. PEC was also combined with hydroxypropilmethylcellulose (HPMC) in different concentrations. The results of the dissolution study showed that PEC could retard the release of famotidin for 10 hours. PEC in combination with HPMC could retard the release of famotidin for 20 hours. Tablet that only contains PEC as matrix could remain buoyant for 12 hours while tablet with combination of PEC and HPMC could remain buoyant for 24 hours.